2007
DOI: 10.1021/jp061633o
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of DFT Methods for Molecular Orbital Eigenvalue Calculations

Abstract: We report how closely the Kohn-Sham highest occupied molecular orbital (HOMO) and lowest unoccupied molecular orbital (LUMO) eigenvalues of 11 density functional theory (DFT) functionals, respectively, correspond to the negative ionization potentials (-IPs) and electron affinities (EAs) of a test set of molecules. We also report how accurately the HOMO-LUMO gaps of these methods predict the lowest excitation energies using both time-independent and time-dependent DFT (TD-DFT). The 11 DFT functionals include th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

36
547
0
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 774 publications
(585 citation statements)
references
References 46 publications
36
547
0
2
Order By: Relevance
“…Calculations were done both in vacuum and with an implicit solvent model of acetonitrile, using ORCA's version of the COSMO method [62]. After geometry optimization, time-dependent DFT calculations were carried out to determine the UV-vis spectra and the HOMO-LUMO gap [42], together with harmonic frequency calculations to evaluate the IR and Raman spectra. The plots of the HOMO and LUMO orbitals were made with the VMD program [63].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Calculations were done both in vacuum and with an implicit solvent model of acetonitrile, using ORCA's version of the COSMO method [62]. After geometry optimization, time-dependent DFT calculations were carried out to determine the UV-vis spectra and the HOMO-LUMO gap [42], together with harmonic frequency calculations to evaluate the IR and Raman spectra. The plots of the HOMO and LUMO orbitals were made with the VMD program [63].…”
Section: Methodsmentioning
confidence: 99%
“…The cyclic voltammogram of 1 in CH 3 CN displays a reversible rsfs.royalsocietypublishing.org Interface Focus 5: 20140083 potentials can be approximated to the highest occupied molecular orbital (HOMO) and lowest unoccupied molecular orbital (LUMO) energy levels, respectively (figure 2b), calculated using quantum chemistry (density functional theory (DFT)) to be separated by 2.1 eV. This value was determined as the lowest energy from the UV-vis spectrum evaluated using a time-dependent DFT method [42]. Plots of the HOMO and LUMO are shown in figure 2b, whereas the calculated spectrum is shown in the electronic supplementary material.…”
Section: Synthesis and Characterization Of A Push -Pull Organic Dyementioning
confidence: 99%
“…65 Zhang and Musgrave have also reported that B3LYP yields lower errors in the LUMO energy of small organic molecules as compared to other DFT methods with a higher percentage of Hartree-Fock exchange. 66 The 6-31+G* basis set is recommended in calculations involving anionic species and was therefore used here. 62 The spatial variation of the electron coupling has been scanned as a function of the x-and y-axes displacement at fixed z = 3.4 Å.…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, the exchange-correlation functional describing the many-body electron interactions is approximated for simplification [1]. However, the functional choice is a very responsible stage, because different functionals may describe various characteristics of a substance in different ways, and the results obtained may not be consistent with each other [2,3]. This is especially true for the nanostructures with a complex carbon-nitrogen atomic structures [4 -9].…”
Section: Introductionmentioning
confidence: 99%